2020
DOI: 10.1073/pnas.2007699117
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and hydroxyapatite binding site of human vitronectin provides insights to abnormal deposit formation

Abstract: The human blood protein vitronectin (Vn) is a major component of the abnormal deposits associated with age-related macular degeneration, Alzheimer’s disease, and many other age-related disorders. Its accumulation with lipids and hydroxyapatite (HAP) has been demonstrated, but the precise mechanism for deposit formation remains unknown. Using a combination of solution and solid-state NMR experiments, cosedimentation assays, differential scanning fluorimetry (DSF), and binding energy calculations, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
4
12
0
Order By: Relevance
“…As predicted by NMR (24), the m1-bound Ca 2+ is not deeply buried within the channel, and locates 0.4-0.8 Å further away from Cl − than m1-bound Na + (Fig. 1C-F; Fig.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As predicted by NMR (24), the m1-bound Ca 2+ is not deeply buried within the channel, and locates 0.4-0.8 Å further away from Cl − than m1-bound Na + (Fig. 1C-F; Fig.…”
Section: Resultssupporting
confidence: 65%
“…Previously, we showed that Ca 2+ binds Vn HX with a dissociation constant in the range of 27 μM (24) and, since this value is approximately ten times higher than the blood concentration of Vn (2.5-5 μM) (1-3) and thirty times lower than the total blood concentration of Ca 2+ (1.3-1.5 mM) (26), we concluded that Vn is Ca 2+ -associated in vivo . Using NMR, we showed that Ca 2+ enhances conformational exchange of Vn on the ms time scale, and by monitoring protein unfolding with DSF and an environment-sensitive fluorescent dye, we showed that Ca 2+ markedly increases the unfolding transition temperature of Vn and, thus, protects the structure from thermal denaturation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delineation of this pathway could facilitate the development of diagnostic, preventive, or therapeutic treatment strategies. Vitronectin has been recognized previously as a promising therapeutic target to regulate complement activation and inflammation [ 111 ] and to prevent ectopic deposits associated with AMD [ 19 ]. Addressing the need to regulate and not simply inhibit pathological angiogenic events in NV-AMD [ 112 ], therapeutic modulation of vitronectin and PAI-1 protein expression, either through genetic or pharmacological approaches, could contribute to the restoration of vascular homeostasis and, thus, help to prevent or treat vascular abnormalities in late stage AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with lipids, glycosaminoglycans, collagens, plasminogen activator inhibitor-1 (PAI-1) and adhesion receptors make vitronectin a multifunctional protein involved in the regulation of a variety of cellular events that are also known to be affected by AMD, such as ECM deposition, cell adhesion and migration, immune response, angiogenesis and fibrinolysis [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Notably, vitronectin has repeatedly been identified as the main component and coordinating factor in the formation of AMD-associated retinal deposits [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%